Direct Synthesis and Catalytic Application of Ordered Mesoporous Ru/C Composites with Homogeneously Dispersed Ruthenium Nanoclusters. Issue 9 (13th July 2016) - Li, Xu; Wang, Xueguang; Huang, Haigen; Chen, Chenju; Zou, Xiujing; Ding, Weizhong; Lu, Xionggang
Abstract: Direct synthesis of metal/carbon nanocomposites with ordered mesoporous frameworks has attracted increasing interest in various applications including catalysis, optics, and electronics. Herein, we demonstrate a simple one‐pot co‐assembly route to synthesize Ru/carbon composites by using resol, ruthenium chloride, and Pluronic F127 as a template with the assistance of 8‐hydroxyquinoline. 8‐Hydroxyquinoline exerts a significant influence on the mesostructure ordering and specific surface area of the Ru/carbon composites. The obtained Ru/carbon materials show well‐ordered hexagonal arrays of mesopores with homogeneously dispersed sub‐2 nm Ru nanoclusters throughout the carbon frameworks, which can efficiently and quantitatively hydrogenated nitrobenzene to aniline with H2 in the absence of solvent for multiple recycling runs without loss of activity. Abstract : Ru ordering : Well‐ordered mesoporous Ru/C composites with homogenously dispersed Ru nanoclusters (sub 2 nm) were prepared by a one‐pot 8‐hydroxyquinoline‐assisted co‐assembly method (see figure). The composites can efficiently and quantitatively hydrogenate nitrobenzene to aniline with hydrogen in the absence of solvent for multiple recycling reactions without loss of catalytic activity.